FUNGSI GAYA BAHASA PERBANDINGAN DAN PERTENTANGAN DALAM PODCAST RINTIK SEDU PADA APLIKASI SPOTIFY - Risnawati Risnawati; Usman Usman; Hasriani Hasriani (Fakultas Bahasa dan Sastra Indoensia, 2023)
The Function of Comparative and Contradictory Language Styles in the Rintik Sedu Podcast on the Spotify application obtains two comparative functions, namely conveying similarities and comparative statements, as well as obtaining two contradictory functions, namely, conveying affirmation and conveying opinions. Conveying similarities is used to express similarities to something in question. Comparative statements are used to express a comparison of something. Conveying an affirmation is used to emphasize something that is considered to be in accordance with the speaker's opinion. Expressing opinions is used to provide advice or opinions on something to someone. This research aims to describe the function of comparative and contradictory language styles in the rintik sedu podcast on the Spotify application. This research uses a qualitative descriptive method obtained through note-taking, reading and documentation techniques. The results of the research found five data with one statement each, two statements of similarities and two statements of comparison